Silver-ammonia complexing, carbonizing and reducing silver-loaded diatom-based composite material as well as preparation and application thereof

By using silver-ammonia complexed carbonized reduction silver-carrier diatom-based composite in the negative electrode material of lithium-ion battery, the problems of poor conductivity and large volume expansion of the existing negative electrode materials are solved, and high conductivity and stable electrochemical performance are achieved.

CN119591111AActive Publication Date: 2025-03-11CENT SOUTH UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411693354.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-03-11
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

Existing lithium-ion battery anode materials such as graphite and silicon have poor conductivity, large volume expansion, and high energy consumption and high carbon emissions in preparation, which limits their large-scale commercial applications.

Method used

The silver-ammonia complexed carbonization-carrying silver-carrying diatom-based composite material was used to embed Ag nanoparticles into the porous structure of diatoms, and the complexing between -NH2 and Ag+ was used to form a highly conductive and stable carbon-silver network structure.

Benefits of technology

The conductivity of SiO2 is significantly improved, the volume expansion of SiO2 during the cycle is suppressed, and excellent electrochemical activity is achieved, opening up new prospects for the development of negative electrode materials for lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591111A_ABST
    Figure CN119591111A_ABST
Patent Text Reader

Abstract

The invention discloses a silver-ammonia complexing, carbonizing and reducing silver-loaded diatom-based composite material as well as preparation and application thereof, in the preparation process of the material, triaminopropyltriethoxysilane (APTES) is adopted as a silicon source required by diatom growth, amino functional groups are introduced to diatom shells, silver ions are added for complexing, and finally carbonization and reduction are performed to obtain the silver-loaded diatom-based composite material. The silver-loaded diatom shell material is obtained and prepared into the lithium ion battery negative electrode material, the conductivity of diatom biological silicon dioxide is greatly improved through evenly-loaded Ag nanoparticles, the lithium ion battery negative electrode material with excellent electrochemical performance is obtained, and the method has the advantages of being simple, convenient, efficient, environmentally friendly and low in consumption; and theoretical guidance is provided for development and utilization of silicon dioxide negative electrode materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of diatom modification application and lithium ion battery negative electrode material preparation, and specifically relates to a silver-ammine complex carbonization reduction silver-carrying diatom-based composite material and its preparation and application. Background Art

[0002] The rapid development of the new energy industry has put forward higher requirements for all aspects of energy storage devices. As the most widely used energy storage component in the market today, the development of negative electrode materials of lithium-ion batteries has always lagged behind that of positive electrode materials. The most widely used graphite negative electrode material in commercial applications is limited by its low theoretical specific capacity (372mAh g -1 ), it is difficult to meet the needs of the current energy market, so various metal oxides or alloy negative electrode materials have emerged. Among them, silicon has a very high theoretical specific capacity (4200mAh·g -1 ) is considered to be the most promising negative electrode material for the next generation of lithium-ion batteries. However, problems such as poor conductivity of silicon and huge volume expansion (300%-400%) during the cycle limit its large-scale commercial application. In addition, the preparation of pure silicon is a high-energy consumption and high-carbon emission process. As a substitute for Si, SiO2 is very abundant on the earth. Although the theoretical specific capacity (1965mAh·g -1 ) is lower than silicon, but still several times that of graphite, and has smaller volume expansion and lower discharge potential, but SiO2 negative electrode materials also have problems such as poor conductivity and low initial coulombic efficiency. For these problems, the common solution is to design nanostructures and composite SiO2 with conductive phases. At present, silicon dioxide has been tested as a highly promising negative electrode material for lithium-ion batteries.

[0003] Diatoms, as a naturally occurring source of SiO2, can absorb dissolved silicon through biomineralization and transform it into an amorphous hydrated silica (SiO2·H2O) shell structure. Their cell walls have a complex hierarchical nanostructured porous SiO2 network. They are widely distributed on the earth and have abundant reserves. They are a very potential source of silica negative electrode materials. At present, in order to solve the problem of poor conductivity of SiO2, SiO2 is usually compounded with carbon or metal with stronger conductivity to improve the conductivity and initial coulombic efficiency of the material. Commonly used composite methods include solid phase self-assembly, hydrothermal method, wet chemical method, etc. Commonly used composite metals are transition metals such as Fe, Co, Ni, and Mn. However, traditional composite methods have problems such as low loading efficiency, uneven distribution, and easy shedding. Therefore, exploring new composite material preparation methods is an urgent need for the application of SiO2 negative electrodes in the field of lithium-ion battery negative electrodes. Summary of the invention

[0004] In view of the problems existing in the prior art, the purpose of the present invention is to provide a silver-ammonia complex carbonization reduction silver-loaded diatom-based composite material and its preparation method and application. The present invention can embed Ag nanoparticles into the surface of SiO2 or its porous structure. The loading efficiency of Ag nanoparticles in the diatom-based composite negative electrode material is higher, the distribution is more uniform, and it is more firm and not easy to fall off. The present invention embeds Ag nanoparticles into the surface of SiO2 or its porous structure for the first time. + Loaded onto the amino-functionalized diatom shell structure, different from the traditional metal material composite method, using -NH2 and Ag + The unique complexation between Ag + The uniform loading onto the porous SiO2 structure surface significantly improves the conductivity of SiO2 and can significantly inhibit the volume expansion of SiO2 during the cycle process, opening up new prospects for the development of negative electrode materials for lithium-ion batteries. The specific technical solutions are as follows:

[0005] A method for preparing a silver-ammine complex carbonization reduction silver-carrying diatom-based composite material comprises the following steps:

[0006] 1) Amino functional modification of diatoms: APTES (triaminopropyltriethoxysilane) was used as a silicon source to culture diatoms;

[0007] 2) Collection and pretreatment of diatoms: The diatoms after cultivation are collected and filtered or centrifuged, and then washed with acid and alcohol in sequence, and the precipitate is collected by solid-liquid separation;

[0008] 3) Preparation of silver-loaded diatom-based composite materials: Add the pretreated diatoms to the Ag + In the solution, after ultrasonic dispersion, the mixture was allowed to stand, and after alcohol washing, the precipitate was separated from the solid and liquid and collected;

[0009] 4) The diatom mixture is precipitated, freeze-dried, and calcined at high temperature in a protective atmosphere to obtain a silver-loaded diatom-based composite material.

[0010] The method described includes: step 1) adding APTES with a concentration of 0.01-0.05 M to diatom F / 2 culture medium at a ratio of 0.2-1.4 mL / L culture medium to culture diatoms.

[0011] Furthermore, the culture period is 7-10 days, the culture temperature is 22-25°C, and the light intensity is 2000-3000lx.

[0012] In the method, step 2) the collected algae liquid is added to at least one of HCl and H2SO4 to wash 1-2 times and then centrifuged to collect the precipitate.

[0013] Furthermore, the acid-washed diatom precipitate is washed 1-2 times with at least one of methanol and ethanol.

[0014] In the method, step 3) the pretreated diatom is added to a silver nitrate solution, ultrasonically dispersed, allowed to stand and then centrifuged to collect the precipitate, washed 1-2 times with at least one of methanol and ethanol and then centrifuged to collect the precipitate.

[0015] Further, 1-2 mL of the pretreated diatom precipitate is added to 20-60 mL of a 0.1 M-0.2 M silver nitrate solution, ultrasonically dispersed for 10-15 minutes, and allowed to stand for 6-12 hours.

[0016] In the method, step 4) freeze-drying the diatom precipitate at -70°C for at least 24 hours.

[0017] The dried diatom powder is heated to 600-900°C at a rate of 5-10°C / min and kept at this temperature for 1-3 hours.

[0018] The invention also provides a silver-carrying diatom-based composite material prepared by the method.

[0019] The present invention also provides application of the silver-loaded diatom-based composite material in negative electrode materials for lithium-ion batteries, and further, is used for the preparation of negative electrode materials for lithium-ion batteries.

[0020] The active material prepared by the present invention is mixed with Super P and PVDF in a mass ratio of 7:2:1 or 7:1.5:1.5 or 8:1:1, and an appropriate amount of N-methylpyrrolidone (NMP) is added, and ball milling is performed at 300-450 r / min for 1-3 hours to obtain a uniformly mixed electrode slurry, and the slurry is coated on a copper foil with a thickness of 25-300 μm, vacuum dried at 80°C, and cut to obtain an electrode sheet. Preferably, the ratio of active material: Super P: PVDF = 7:2:1, ball milling is performed at 300 r / min for 3 hours, and the slurry coating thickness is 50 μm.

[0021] Furthermore, the cut electrode sheets are placed on the lower shell of the battery in an argon-filled glove box, 1 to 2 drops of electrolyte are dripped on the surface of the electrode sheets, a diaphragm is placed, and 1 to 2 drops of electrolyte are dripped again, and finally the lithium sheets are placed, the battery cover is covered, and the battery is sealed on a button battery packaging machine to complete the battery assembly.

[0022] The main difference between the present invention and the method disclosed in the prior art is that: diatoms, a bio-based SiO2 material with natural regular nanostructures, are used, aminosilane is used as the silicon source required for the growth of diatoms, -NH2 is introduced into diatoms, and Ag is converted into silane through the coordination complexation between -NH2 and the sub-group metal. +After being bonded to the surface of the diatom shell structure and then subjected to high-temperature calcination and carbonization reduction in a protective atmosphere, a conductive layer composed of a carbon-metal network is formed. The Ag nanoparticles in the diatom-based composite negative electrode material prepared by the method of the present invention have a higher loading efficiency, a more uniform distribution, and are more solid and not easy to fall off. On the basis of the prior art, the present invention further improves the conductivity of silicon dioxide, and at the same time suppresses the volume expansion of silicon dioxide during the cycle process through the carbon-silver network structure. The development of lithium-ion battery negative electrode materials with excellent electrochemical activity is achieved. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 These are transmission electron microscope images of Comparative Example 1 (a), Comparative Example 2 (b), Example 1 (c), Example 2 (d) and Example 3 (e) of the present invention. The surface of the diatom shell of Comparative Example 1 is smooth and unloaded, while the surface of the diatom shell of Comparative Example 2, Example 1, Example 2 and Example 3 is distributed with Ag nanoparticles.

[0024] Figure 2 The XRD patterns of Comparative Example 1, Comparative Example 2, Example 1, Example 2 and Example 3 of the present invention are shown in FIG.

[0025] Figure 3 The comparative examples 1, 2, examples 1, 2 and 3 of the present invention are shown in FIG. -1 Charge and discharge curves at different current densities.

[0026] Figure 4 These are cyclic voltammetry test curves of Comparative Example 1, Comparative Example 2, Example 1, Example 2 and Example 3 of the present invention.

[0027] Figure 5 These are rate performance curves of Comparative Example 1, Comparative Example 2, Example 1, Example 2, and Example 3 of the present invention.

[0028] Figure 6 These are the electrochemical impedance spectroscopy test spectra of Comparative Example 1, Comparative Example 2, Example 1, Example 2 and Example 3 of the present invention.

[0029] Figure 7 TEM images of Comparative Example 3(a), Comparative Example 4(b) and Comparative Example 5(c) of the present invention.

[0030] Figure 8 Comparative Examples 3, 4 and 5 of the present invention are shown in Figure 1 at 100 mA·g -1 Charge and discharge curves at different current densities. DETAILED DESCRIPTION

[0031] In order to explain in detail the preparation method of the material of the present invention and its application in the negative electrode material of lithium ion batteries, further description is given below in conjunction with specific embodiments and accompanying drawings.

[0032] Example 1

[0033] (1) APTES with a concentration of 0.01 M was added to the culture medium at a ratio of 1.33 mL of silicon source solution / L of diatom F / 2 culture medium to culture diatoms. The culture period was 10 days, the culture temperature was 25° C., the light intensity was 2500 lx, and the culture was static.

[0034] (2) The diatoms cultured in (1) are collected to obtain an enriched algae solution, and 5% dilute hydrochloric acid is added to the algae solution and the solution is immersed for 3 hours to obtain a hydrochloric acid diatom mixed solution.

[0035] (3) The hydrochloric acid diatom mixture in (2) was centrifuged at 10,000 r / min for 10 min, the supernatant was removed, and the diatom precipitate was collected.

[0036] (4) Wash the diatom precipitate in (3) twice with anhydrous ethanol, and then collect the precipitate by centrifugation at 10,000 rpm for 10 min.

[0037] (5) Add 0.1 M silver nitrate solution to the diatom precipitate in (2), disperse by ultrasonic for 10 min, and let stand for 6 h.

[0038] Dosage: Add 20 mL of silver nitrate solution to 2 mL of diatom precipitate, wash with anhydrous ethanol and collect the precipitate by solid-liquid separation.

[0039] (6) The collected diatom mixture was precipitated and freeze-dried at -70°C for at least 24 hours to obtain an amino-functionalized silver-loaded diatom mixture.

[0040] (7) The diatom mixture dried in (6) was heated to 600° C. at a rate of 5° C. / min and calcined for 3 h under an argon atmosphere to obtain a silver-loaded diatom-based composite material.

[0041] (8) The phase composition of the silver-loaded diatom composite material was analyzed by XRD. The results are as follows Figure 2 As shown, the XRD results show obvious Ag single-element diffraction peaks and broad diffraction peaks of amorphous silica. The components of the composite material are SiO2, C and Ag single elements, and the required silver-loaded diatom-based composite material (AFD@C-Ag-20) is successfully synthesized.

[0042] (9) The surface structure of the silver-loaded diatom shell and the Ag loading were observed by transmission electron microscopy. A large number of Ag nanoparticles were observed to be loaded on the surface of the diatom shell structure. The diameter of the Ag nanoparticles was 5-20 nm and they were evenly distributed. The silver-ammonia complex carbonization reduction silver-loaded diatom composite material (AFD@C-Ag-20) was successfully synthesized.

[0043] (10) The active composite material was mixed with Super P and PVDF in a mass ratio of 7:2:1, and an appropriate amount of N-methylpyrrolidone (NMP) solvent was added. The mixture was ball-milled at 300 r / min for 3 h to obtain a uniformly mixed electrode slurry. The slurry was coated on a copper foil with a thickness of 50 μm, dried in a vacuum at 80 °C, and cut into circular electrode sheets with a diameter of 12 mm;

[0044] (11) Place the cut electrode sheet into the lower shell of the battery in an argon-filled glove box, drip 1 drop of electrolyte on the surface of the electrode sheet, place a separator, then drip 1 drop of electrolyte, and finally place the lithium sheet, cover the battery cover, and seal it on a button battery packaging machine to complete the battery assembly;

[0045] (12) The assembled battery was subjected to impedance spectroscopy testing on a Gamry electrochemical workstation with a test frequency range of 100kHz to 10MHz. The impedance spectroscopy results are as follows: Figure 6 As shown, the charge transfer impedance of AFD@C-Ag-20 is lower than that of carbon composite diatom material (DBS@C).

[0046] (13) The assembled battery was subjected to a cycle charge and discharge test on the LAND battery charge and discharge test system, with the test voltage range of 0.001 to 3.0 V (vs. Li / Li + ), the current density is 100 mA g -1 , the charge and discharge curves are as follows Figure 3 As shown, the electrode is at 100 mA g -1 After 80 cycles at the current density of 644.5 mAh g -1 The specific capacity and cycle stability are good. The rate test results are as follows Figure 5 As shown in the figure, the rate performance of AFD@C-Ag-20 is better than that of DBS@C. The impedance spectrum test results show that AFD@C-Ag-20 has a large impedance and poor rate performance.

[0047] Example 2

[0048] The difference between Example 2 and Example 1 is only that:

[0049] The amount of AgNO3 solution added in step (5) was 40 mL, and the remaining steps remained unchanged.

[0050] The phase composition of diatom composite materials was analyzed by XRD. Figure 2 As shown, there are obvious diffraction peaks of Ag and broad diffraction peaks of amorphous silica, indicating that the components of the composite material are SiO2, C and Ag, and the required silver-loaded diatom-based composite material (AFD@C-Ag-40) is successfully synthesized.

[0051] Through transmission electron microscopy, it was observed that there were a large number of Ag nanoparticles distributed on the surface of the diatom shell. The diameter of the Ag nanoparticles was about 5-20nm and they were evenly distributed on the surface of the diatom. -1 After 80 cycles at the current density of ~661 mAh g -1 The specific capacity and cycle stability are good. The rate test results are as follows Figure 5 As shown in the figure, the rate performance of AFD@C-Ag-40 is better than that of DBS@C and AFD@C-Ag-20. The impedance test results show that AFD@C-Ag-40 has low charge transfer impedance and good rate performance.

[0052] Example 3

[0053] The difference between Example 3 and Examples 1 and 2 is only that:

[0054] The amount of AgNO3 solution added in step (3) is 60 mL. The remaining steps remain unchanged. The phase composition of the diatom composite material was analyzed by XRD. The results are as follows Figure 2 As shown, it shows obvious Ag single substance diffraction peaks and broad diffraction peaks of amorphous silica. The composite material consists of SiO2, C and Ag single substances. The desired silver-loaded diatom-based composite material (AFD@C-Ag-60) was successfully synthesized. Through transmission electron microscopy, it was observed that a large number of Ag nanoparticles were distributed on the surface of the diatom shell, which was more than AFD@C-Ag-40. The diameter of the Ag nanoparticles was 5-20nm and was evenly distributed on the surface of the diatom. The electrode was 100mA·g -1 After 80 cycles at the current density of ~765 mAh g -1 The specific capacity and cycle stability are good. The rate test results are as follows Figure 5 As shown in the figure, the rate performance of AFD@C-Ag-60 is better than that of DBS@C, AFD@C-Ag-20 and AFD@C-Ag-40. The impedance test results show that AFD@C-Ag-60 has low charge transfer impedance and excellent rate performance.

[0055] Comparative Example 1

[0056] The difference between Comparative Example 1 and Example 1 is only that:

[0057] The collected algae liquid after culture was directly freeze-dried to obtain dry diatom powder, which did not react with AgNO3 solution. The other steps were the same to prepare a diatom composite material (DBS@C) without Ag loading. The XRD results showed a broad diffraction peak at about 22°, corresponding to the amorphous silica structure, and a carbon diffraction peak at 25.8°, without the diffraction peak of Ag single substance. The above experimental steps were used to prepare electrodes, assemble batteries and test electrochemical performance as a comparative example. Figure 1 a Transmission electron microscopy image shows that the surface of DBS@C is smooth and unloaded, and a hierarchical porous silica structure is observed. The charge transfer impedance of the electrode is large. -1 After 80 cycles, ~366 mAh g -1 The specific capacity and rate performance are poor.

[0058] Comparative Example 2

[0059] The difference between Comparative Example 2 and Example 3 is only that:

[0060] The silicon source used in step 1 is the inorganic silicon source Na2SiO4·9H2O (equivalent to the silicon of the organosilicon in Example 3). The remaining steps are the same to prepare the silver-loaded diatom composite material PD@C-Ag-60, and the above experimental steps are used for electrode preparation, battery assembly and electrochemical performance testing as a comparative example. XRD results show that the main components of the DBS@C material are amorphous silicon dioxide, elemental silver and carbon. The results of transmission electron microscopy show that there is a small amount of Ag nanoparticles loaded on the surface of PD@C-Ag-60. The Ag loading is less than that in Example 3, and the electrochemical performance is also poor. The charge transfer impedance of the electrode is large, and at 100mA·g -1 After 80 cycles, ~474 mAh g -1 The specific capacity and rate performance are poor.

[0061] Comparative Example 3

[0062] The difference between Comparative Example 3 and Example 3 is only that:

[0063] The silicon source used in step 1 is a mixture of tetramethoxysilane and (3-mercaptopropyl)trimethoxysilane with equal Si content, the ratio of tetramethoxysilane to (3-mercaptopropyl)trimethoxysilane in the mixture is 3:1, and the remaining steps are the same to prepare a silver-loaded diatom composite material (3-SH-Ag-60). The microstructure of 3-SH-Ag-60 was observed by scanning electron microscopy, and it was found that a large number of Ag nanoparticles were distributed on the surface of the diatom shell, but the number of nanoparticles was less than that in Example 3, because the adsorption of -SH on Ag+ is weaker than the coordination bond between -NH2 and Ag. It was prepared as a negative electrode material for lithium-ion batteries and the electrochemical performance was tested. 3-SH-Ag-60 was 100mA·g -1 After 80 cycles at a current density of about 628.4 mAh g -1 The discharge specific capacity is lower than that of Example 3.

[0064] Comparative Example 4

[0065] The difference between Comparative Example 4 and Example 3 is only that:

[0066] The diatom precipitate after acid washing and alcohol washing was soaked in 10% H2O2 for 0.5h, collected by centrifugation, and 2mL of diatom precipitate was added to 60mL of 0.1M AgNO3 solution, and 1.33mL of 0.1M APTES was added. After ultrasonic dispersion for 10min, it was allowed to stand for 6h, and washed with deionized water instead of anhydrous ethanol. The rest of the steps were the same, and the silver-loaded diatom-based composite material (DBS@C-Ag-60) was prepared. The microstructure of the silver-loaded diatom shell ( Figure 7 b), it was found that a large number of Ag single-substance nanoparticles were distributed on the surface of the diatom shell, and the Ag nanoparticles were loaded evenly, but the loading amount was less than that in Example 3, because the pretreatment step would destroy some Si-OH on the inner and outer surfaces of the diatom shell, resulting in a decrease in the number of -OH grafted with APTES, thereby causing a decrease in the loading efficiency of Ag. After preparing it as a negative electrode material for lithium-ion batteries, the electrochemical performance test was carried out. At 100mA·g -1 After 80 cycles, the capacity is 700.2 mAh g -1 The specific capacity is lower than that of Example 3.

[0067] Comparative Example 5

[0068] The difference between Comparative Example 5 and Comparative Example 4 is that:

[0069] The diatom precipitate after acid washing and alcohol washing was soaked in 10% H2O2 for 0.5h, collected by centrifugation, 2mL of diatom precipitate was added to 60mL of 0.1M AgNO3 solution, and 1.33mL of 0.1M APTES and 20mL of anhydrous ethanol were added. After ultrasonic dispersion for 10min, it was allowed to stand for 6h. The collected diatom precipitate was freeze-dried without high-temperature calcination. The other steps were the same to prepare a silver-loaded diatom composite material (DBS-Ag-60). The microstructure of the silver-loaded diatom shell was observed by transmission electron microscopy ( Figure 7 c) It was found that Ag existed in the form of aggregated clusters on the diatom shells, with uneven distribution. A small amount of Ag crystals could be observed in the aggregated clusters, and the particle size was small, between 2-5nm. There was a large amount of low-conductivity organic biomass on the surface of the uncarbonized diatom shells. After preparing it as a negative electrode material for lithium-ion batteries, the electrochemical performance test showed that at 100mA·g -1 After 80 cycles, the battery capacity is 249.4 mAh g -1 The specific capacity and cycle performance are poor.

Claims

1. A method for preparing a silver-loaded diatom-based composite material by silver-ammine complex carbonization reduction, characterized in that: The following steps are involved: 1) Amino functional modification of diatoms: APTES was used as a silicon source to culture diatoms; 2) Collection and pretreatment of diatoms: After the culture is completed, the algae solution is filtered or centrifuged, and then washed with acid and alcohol in sequence. collecting the precipitate by solid-liquid separation; 3) Preparation of silver-loaded diatom-based composite material: adding the pretreated diatom to the silver ion solution, dispersing it by ultrasonication, letting it stand, washing it with alcohol, separating the solid and the liquid, and collecting the precipitate; 4) The diatom mixture is precipitated, freeze-dried, and calcined at high temperature in a protective atmosphere to obtain a silver-loaded diatom-based composite material.

2. The preparation method according to claim 1, characterized in that: Step 1) APTES with a concentration of 0.01-0.05 M is added to diatom F / 2 culture medium at a ratio of 0.2-1.4 mL / L culture medium to culture diatoms.

3. The preparation method according to claim 1 or 2, characterized in that: Step 1) The culture period is 7-10 days, the culture temperature is 22-25°C, and the light intensity is 2000-3000lx.

4. The preparation method according to claim 1, characterized in that: Step 2) adding at least one of HCl and H2SO4 to the collected algae solution for washing 1-2 times, and then centrifuging to collect the precipitate; washing the diatom precipitate after acid washing with at least one of methanol and ethanol for 1-2 times.

5. The preparation method according to claim 1, characterized in that: Step 3) adding the pretreated diatom to a silver nitrate solution, dispersing it by ultrasonication, collecting the precipitate by centrifugation after standing, washing it 1-2 times with at least one of methanol and ethanol, and collecting the precipitate by centrifugation.

6. The preparation method according to claim 1 or 5, characterized in that: Step 3) Add 1-2 mL of the pretreated diatom precipitate to 20-60 mL of 0.1 M-0.2 M silver nitrate solution, ultrasonically disperse for 10-15 min, let stand for 6-12 h, and collect the precipitate by solid-liquid separation.

7. The preparation method according to claim 1 or 6, characterized in that: Step 4) freeze-drying the diatom mixture at -70°C for at least 24 hours; heating the dried diatom powder to 600-900°C at a rate of 5-10°C / min and keeping the temperature for 1-3 hours.

8. A silver-carrying diatom-based composite material, characterized in that: Prepared by the method described in any one of claims 1 to 7.

9. The use of the silver-carrying diatom-based composite material according to claim 8, characterized in that: Used in the preparation of negative electrode materials for lithium-ion batteries.

Citation Information

Patent Citations

  • Silver-loaded diatom shell antibacterial ceramic filter core and preparation method thereof

    CN111943717A

  • Method for reducing solubility of diatom shell, low-solubility diatom and application

    CN115926991A

  • Diatom-based composite material coated with Mn2SiO4 as well as preparation method and application of diatom-based composite material

    CN118231619A

  • Diatomaceous energy storage devices

    EP2899784A1

  • Embodiments of a composition comprising diatom frustules and a method for making and using

    WO2014121134A2